If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x+6)=2(12+x)
We move all terms to the left:
2(x+6)-(2(12+x))=0
We add all the numbers together, and all the variables
2(x+6)-(2(x+12))=0
We multiply parentheses
2x-(2(x+12))+12=0
We calculate terms in parentheses: -(2(x+12)), so:We get rid of parentheses
2(x+12)
We multiply parentheses
2x+24
Back to the equation:
-(2x+24)
2x-2x-24+12=0
We add all the numbers together, and all the variables
-12!=0
There is no solution for this equation
| 76=20x-4 | | 13(-16-11)-18f=161f-208 | | 8b-3=21 | | 11w-2w=8 | | 5(x-2)-6x=13 | | 2m-8=6m+8 | | 8x+10=8x+8-2x | | 5(3x+7)=-46+6 | | 2.3x+2.8=−1.2x+9.8 | | Y+7=10(x+10) | | -7/4=-7/4+2n/9 | | 34+x180=90 | | -9(x-2)+2=16-7x | | 19-5h=4 | | 2x-4=-2x+6 | | 7-3k=1-3k | | 2x+x+4=19 | | -46t-23=46t+23 | | x2=9/400 | | 2x+7=5x-3(x-4) | | 10+x/4=22 | | 1x/2-9=7.5+6x | | -24=-4(2x-4) | | -11c+12c—15c-3c=-13 | | X^2+3+2x+4=15 | | 3x+216=2x | | k-3=7/9 | | 8k+4=8k | | 3(x+2(=-3x+6 | | -16+2=-2(x+8) | | 4(x+3)+10(x-3)=10 | | 4x=-8x+12 |